Host defences against avian brood parasitism: an endocrine perspective - Abolins-Abols, Mikus (Proc Biol Sci, 2018)
Host defences against avian brood parasites are the outcome of well-documented coevolutionary arms races, yet important questions about variation in hosts' antiparasitic response traits remain poorly understood. Why are certain defences employed by some species or individuals and not by others? Here, we propose that understanding variability in and the evolution of host defences can be facilitated by the study of the underlying physiological mechanisms. Specifically, because antiparasitic strategies involve behaviours that have been shown to be hormonally regulated in other contexts, we hypothesize that host responses to brood parasites are likely to be mediated by related endocrine mechanisms. We outline the hallmarks of the endocrine bases of parasite defence-related avian behaviours, review the current understanding of antiparasitic host tactics and propose testable hypotheses about the hormonal mechanisms that may mediate host defences. We consider these mechanisms in a life-history framework and discuss how endocrine factors may shape variation in host defences. By providing a hypothesis-driven mechanistic framework for defences against parasitism, this perspective should stimulate the study of their endocrine bases to enhance our understanding of the intricate arms races in avian host–parasite systems.